More than wordplay: Human geography and human intelligence - KIȘ , Alexandru (International Journal of Legal and Social Order, 2023)
This article delves into the critical role of geography in military operations and intelligence, examining the significance of geographical features in military strategies and engagements. The focus is directed towards human geography and its intricate connection with intelligence operations. Population demographics, cultural diversity, and societal dynamics play a pivotal role in shaping intelligence collection and analysis. The final part of the paper takes a forward-looking perspective, exploring the evolving landscape of Human Intelligence (HUMINT) within the anthroposphere of the future. It delves into how intelligence agencies adapt to an ever-changing world, where geography remains a constant but is coupled with digital advancements, global connectivity, and emerging threats.